CRITERIA OF COMPACT CONVEX SETS' FINITE DIMENSIONALITY - Baghdasarova, G. A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2002)
Let A be a compact convex subset of a locally convex X space, EnA, n≥1, be a set on n-extremaly points of the A set. In the present note criteria of the A set's finite dimensionality are formulated and proved in terms of the EnA sets.